Pengaruh Harga, Promosi dan Kualitas Pelayanan terhadap Minat Beli pada Toko Yusie Collection Kabupaten Bireuen - Nur Halimah; Yusrawati Yusrawati; Al Mahfud Saputra (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the influence of price, promotion, and service quality on consumers’ purchase intention at Yusie Collection Store in Bireuen Regency, Aceh. This research employs a quantitative approach using survey data collected from consumers who have purchased fashion products at the store. Because the total population was unknown, the sample size was determined using the Lemeshow formula, resulting in 100 respondents selected through accidental sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with the assistance of SPSS software. The results show that price, promotion, and service quality have a positive and significant effect on purchase intention. Price has a regression coefficient of 0.464 (p < 0.05), promotion has a coefficient of 0.509 (p < 0.05), and service quality has a coefficient of 0.246 (p < 0.05). Among these variables, promotion has the strongest influence on consumers’ purchase intention. Furthermore, the coefficient of determination (R²) indicates that price, promotion, and service quality simultaneously explain 99.6% of the variance in purchase intention, while the remaining 0.4% is influenced by other factors not included in this study. These findings highlight the importance of effective promotional strategies, competitive pricing, and high-quality service in enhancing consumers’ purchase intention in the retail fashion sector.